Dietary Calcium Had No Reducing Effect on Body Fat and Weight Gain in Sprague-Dawley Rats - Malekzadeh, J.M.; Keshavarz, S.A.; Siassi, F.; Eshraghian, M.; Kadkhodaee, M.; Dorosty, A.R.; Aliehpour, A.; Chamari, M. (Pakistan Journal of Nutrition, 2007)
Recently, studies have focused on the effects of dietary calcium on the weight and fatness. Some of these studies have indicated that there is negative relationship between dietary calcium and body fat, while others have reported no such effects. There are also controversies over serum parathyroid hormone, as its mechanism, on body fat and weight. The objective of the present study was to evaluate the effects of three dietary calcium levels (0.2%, 0.5% or 1.2% Ca2+) on body fat and weight gain in male Sprague-Dawley rats, using same diet composition for nutrients other than calcium. The study duration was 72 days. At the end, truncal blood samples were drawn from decapitated rats to measure the effects of diets on serum calcium, PTH and vitamin D. The carcasses were minced and homogenized to measure their body fat percent by the methods of Soxhelet. There were no significant effects of dietary calcium on food intake (p>0.05), body weight gain (p>0.05) or carcass fat content (p>0.05), while the serum PTH levels were inversely related to calcium intake (p